2020
DOI: 10.9734/ijpr/2020/v5i130122
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity and Phytochemical Screening of Cymbopogon citratus, Cajanus cajan and Plectranthus amboinicus Leaves Collected in Guyana, South America

Abstract: Aims: Medicinal plants have been a fundamental part of the human health since existence. Guyana is surrounded high in the green shoulder of northern South America and shares Amazon River and Amazon Forest. South American population use plant extracts obtained from traditional medicinal plants as treatment for many infectious diseases. The study aimed to estimate antifungal property and chemical composition of the three medicinal plants Cymbopogon citratus (lemongrass), Cajanus cajan (pigeon pea) and Plectranth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Although, the recent study shown inhibition zone around 30 mm at the higher concentration, the wider inhibition zone may due to the higher concentrations that were used in the recent study than in the previous study. The antibacterial activity of Indian borage leaf may be due to the presence of some phytochemicals like phenolic compound which has antimicrobial activity 5,9,10 CONCLUSION Overall, ethanol extract of Indian borage leaves had potential antibacterial activity against Bacillus cereus. This antibacterial activity increase followed by the increase of the concentration.…”
Section: Degree Of Antimicrobial Activitymentioning
confidence: 99%
“…Although, the recent study shown inhibition zone around 30 mm at the higher concentration, the wider inhibition zone may due to the higher concentrations that were used in the recent study than in the previous study. The antibacterial activity of Indian borage leaf may be due to the presence of some phytochemicals like phenolic compound which has antimicrobial activity 5,9,10 CONCLUSION Overall, ethanol extract of Indian borage leaves had potential antibacterial activity against Bacillus cereus. This antibacterial activity increase followed by the increase of the concentration.…”
Section: Degree Of Antimicrobial Activitymentioning
confidence: 99%